2010
DOI: 10.1016/j.acra.2010.01.006
|View full text |Cite
|
Sign up to set email alerts
|

Gold Nanoparticle Contrast in a Phantom and Juvenile Swine

Abstract: The purpose of this study was to demonstrate the application of gold nanoparticles (AuNP) as a contrast agent for a clinical x-ray computed tomography system using a phantom and using juvenile swine. A tissue-mimicking phantom with spherical inclusions containing known concentrations of gold was scanned. Swine were injected with gum Arabic stabilized gold nanoparticles (GA-AuNP), up to 85 mg kg −1 body weight. CT scans were performed prior to and after the injections. Changes in HU values between pre-and post-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 83 publications
(27 citation statements)
references
References 21 publications
1
26
0
Order By: Relevance
“…AuNp were first described by Hainfield et al (2006) for small animal imaging using X-rays and have since become available commercially for preclinical use as AuroVist (Nanoprobes Inc., NY). The work of Boote et al (2010) demonstrated the application of AuNp as a contrast agent with a clinical CT scanner. The potential of using Au for molecular imaging with CT also has been recognized in cancer (Popovtzer et al , 2008; Reuveni et al , 2011; Ghann et al , 2012; Chanda et al , 2011).…”
Section: Introductionmentioning
confidence: 99%
“…AuNp were first described by Hainfield et al (2006) for small animal imaging using X-rays and have since become available commercially for preclinical use as AuroVist (Nanoprobes Inc., NY). The work of Boote et al (2010) demonstrated the application of AuNp as a contrast agent with a clinical CT scanner. The potential of using Au for molecular imaging with CT also has been recognized in cancer (Popovtzer et al , 2008; Reuveni et al , 2011; Ghann et al , 2012; Chanda et al , 2011).…”
Section: Introductionmentioning
confidence: 99%
“…DLS studies of the AuNPs revealed an increase in the hydrodynamic diameter as the serum proteins form the monolayer. The measurement of charge on NPs, zeta-potential (ζ), provides crucial information on the stability of the NP dispersion [22][23][24][25]. The magnitude of the measured ζ is an indication of the repulsive forces that are present and can be used to predict the long-term stability of the nanoparticulate dispersion.…”
Section: Np Size Characterization and Size Distributionmentioning
confidence: 99%
“…Gold nanostructures are often used to overcome the limitations found with standard contrast agents [359][360][361][362]. In addition to their biocompatibility, Au nanoparticles have longer in vivo circulation times during the imaging process and in some cases faster elimination time post-procedure [356,[363][364][365].…”
Section: Imagingmentioning
confidence: 99%